ANALYSIS OF FACTORS AFFECTING THE TRANSACTION COSTS OF RICE FARMERS IN THE PERSPECTIVE OF ISLAMIC ECONOMICS - Arif Dwi Wibowo; M Yusuf Bahtiar; Ersi Sisdianto (JURNAL PROFIT, 2025)
This study aims to analyze the factors that influence the transaction costs of rice farmers in the perspective of Islamic economics in Gadingrejo, namely uncertainty, social networks, and frequency. The methodology used in this study is quantitative associative. The data collection technique uses a questionnaire with a SEM PLS approach using SmartPLS software. The results of this study indicate that uncertainty, social networks, and frequency among farmers in Gadingrejo have a positive and significant effect on transaction costs. This result can be concluded because the calculated F (54.5) > table F (2.77). The contribution of this study is the understanding that transaction costs in Islamic economics do not only cover financial aspects but also social aspects such as justice, trade balance, and business ethics in accordance with Islamic principles.